Nickel-Encapsulated Carbon Nanotubes Modified Boron Doped Diamond Hybrid Electrode for Non-Enzymatic Glucose Sensing. Issue 3 (1st January 2018) - Long, Hangyu; Li, Can; Deng, Zejun; Wang, Yijia; Hu, Naixiu; Meng, Lingcong; Xie, Youneng; Wei, Qiuping; Yu, Zhiming; Zhang, Shugen
Abstract : A hybrid non-enzymatic glucose sensor made by incorporating boron doped diamond (BDD) film electrode with nickel (Ni)- encapsulated carbon nanotubes (CNTs) were facilely fabricated. The CNTs were grown directly on BDD films in the presence of pre-sputtered Ni layer as a catalyst by hot-filament chemical vapor deposition. The morphology and composition of the hybrid structure were assessed by scanning electron microscopy and Raman spectroscopy. As Ni layer thickness increased, the CNTs were less covered on the surface and the length of CNTs increased. The Ni particles were encapsulated into a large number of CNTs. Electrochemical results indicated that this hybrid structure significantly improved the electrochemical performance of BDD due to the increased specific surface area and synergistic effect of Ni and CNTs. The optimized glucose sensor revealed two broad linear range of 1.25 μM - 0.49 mM and 0.49 mM- 6.79 mM, with a high sensitivity of 1642.20 μA mM −1 cm −2 (R 2 = 0.9988) and 1374.4 μA mM −1 cm −2 (R 2 = 0.9969) respectively. In addition, the hybrid electrode exhibited a low limit of detection which was 1.0 μM (S/N = 3), and good selectivity and stability.